STUDI KELAYAKAN ASPEK STRATEGIS DESA WISATA TEMBI UNTUK MENINGKATKAN PARIWISATA DAN PEREKONOMIAN KABUPATEN BANTUL YOYAKARTA - Isdarmanto, Isdarmanto (Kepariwisataan: Jurnal Ilmiah, 2016)
Local community development and tourism through tourist village nowadays is currently promoted and developed by the local government, it has been committed in accordance with regional autonomy program and it was launched a few years ago, so that the development and improvement of regional income seriously needed the responsibility of local governments entirely. The existence of the tourist village of Tembi, further more who became one of the prospects for tourism in the district of Bantul. Potentially tourist village of Tembi which has a unique cultural heritage of indigenous Java, as well as custom program learning of center Javanese culture by the meaning of the noble values of a custom still believe until now. In addition, the tourist village of Tembi also adapt to the developments in field of science and technology. The prospects of potential tourist village of Tembi, it still has not been able to be developed and properly noticed by the actors of society in particular tourism of tourist village Tembi with their own environment, in case this is precisely the right moment to lift the tourism program in the world heritage aspect. To the authors are very interested to do research so as to provide answers about why the potential of the tourist village of Tembi yet to be developed and how the future development of solutions. And so as to provide concrete strategic measures and appropriate environment for the community to realize the tourist village of Tembi and motivate communities to take advantage of business interests family in particular, and in general for the future tourism development and Bantul city become an icon of Yogyakarta tourism. Keywords: Local community, Tourist village of Tembi